Monetary, Food, and Social Rewards Induce Similar Pavlovian-to-Instrumental Transfer Effects - Lehner, Rea; Balsters, Joshua H.; Herger, Andreas; Hare, Todd A.; Wenderoth, Nicole (Frontiers in Behavioral Neuroscience, 2017)
Multiple types of reward, such as money, food, or social approval, are capable of driving behavior. However, most previous investigations have only focused on one of these reward classes in isolation, as such is it not clear whether different reward classes have a unique influence on instrumental responding or whether the subjective value of the reward, rather than the reward type per se, is most important in driving behavior. Here, we investigate behavior using a well-established reward paradigm, Pavlovian-to-instrumental transfer (PIT), and three different reward types; monetary, food, and social rewards. The subjective value of each reward type was matched using a modified Becker-DeGroot-Marschak (BDM) auction where subjective reward value was expressed through physical effort using a bimanual grip force task. We measured the influence of reward-associated stimuli on how participants distributed forces between hands when reaching a target effort range on the screen bimanually and on how much time participants spent in this target range. Participants spent significantly more time in the target range (15 % ± 2 % maximal voluntary contraction) when a stimulus was presented that was associated with a reward used during instrumental conditioning or Pavlovian conditioning compared to a stimulus associated with a neutral outcome (i.e. general PIT). The strength of the PIT effect was modulated by subjective value (i.e. individuals who showed a stronger PIT effect rated the value of rewards more highly), but not by reward type, demonstrating that stimuli of all reward types were able to act as appetitive reinforcers and influenced instrumental responding, when matched to the same subjective reward value. This is the first demonstration that individually matched monetary, food and social rewards are equally effective as appetitive reinforcers in PIT. These findings strengthen the hypotheses that the subjective value is crucial for how much reward-associated stimuli influence behavior.